Frequency of metastasis to the submandibular gland among patients with oral squamous cell carcinomas - Rafael Michel Coca; Dianet Pérez Arechaga; Dadonim Vila Morales; Yuniesky Jiménez Rodríguez; Ernesto Márquez Rancaño; Reinaldo Delís Fernández (Editorial Ciencias Médicas, 2016)
Introduction: the possibility of metastasis to the submandibular gland in patients with oral squamous cell carcinomas is a novel topic not frequently dealt with in scientific research. This is the first time a study of this sort is conducted in Cuba. Objective: determine the frequency of metastasis to the submandibular gland among patients with oral squamous cell carcinomas undergoing the surgical procedure of cervical lymph node dissection. Methods: a prospective descriptive study was conducted. Non-probabilistic sampling was used to select 43 patients attending head and neck consultation at the Maxillofacial Surgery Service of Arnaldo Milián Castro Provincial Clinical Surgical University Hospital in Villa Clara from January 2011 to July 2014. Inclusion criteria were a diagnosis of oral squamous cell carcinoma, cervical lymph node dissection as primary onco-specific treatment, and willingness to participate in the study. Results: sixty-eight submandibular glands were obtained from the sample of 43 patients undergoing exeresis of the primary tumor and cervical lymph node dissection. Floor of mouth tumors and early clinical stages I-II represented 53.5 % and 55.8 % of the sample, respectively. Submandibular gland involvement was found in only one patient (2.3 %) and it was due to direct invasion of the capsule by adjacent metastatic lymph nodes. Conclusion: submandibular gland metastasis was not found in any case, which could suggest the preservation of this gland when cervical lymph node dissection is performed.